Inner world of counseling with Carl Rogers - Rogers, Carl R. (Carl Ransom), 1902-1987.; Resnikoff, Arthur; Whiteley, John M.; American Personnel and Guidance Association; Insight Media (Firm); Sinostar Ltd. (New York : Distributed by Insight Media ; Hong Kong : Sinostar Ltd.)
Two interviews in which Dr. Carl R. Rogers uses client-centered counseling in interviews with Sylvia, who discusses her problems as a divorcee and single parent, and her fears about going to work full-time. Through use of freeze frames and voiceover commentary, Sylvia comments on her feelings at various points in the interview, and Dr. Rogers discusses his counseling techniques and the feelings Sylvia seems to be expressing. The second of the two interviews is first on the video.
Pt. 1 (28 min.) -- pt. 2 (31 min.)
Title from disc label.
Series created by John M. Whiteley.
Copyright held by American Personnel and Guidance Association.
Original released in 1980.
DVD.
NTSC.
Keywords: Client-centered psychotherapy; Psychotherapy; Documentary films